Corrosion behaviour of Nitinol alloy coated with alkylsilanes and polypyrrole - Flamini, Daniel Omar (2014)
Nitinol (equiatomic Ni and Ti alloy (NiTi)) substrate was modified using a coating system formed by a self-assembled film of alkylsilane compounds (propyltrichlorosilane (C3H7SiCl3) or octadecyltrichlorosilane (C18H37SiCl3)) and polypyrrole (PPy) doped with sodium bis(2-ethylhexyl) sulfosuccinate (Aerosol OT or AOT). The combination of alkylsilanes and the presence of a voluminous molecule like AOT entrapped into the PPy films improve the pitting corrosion resistance of the substrate in chloride solution. The best performance was achieved with the longest alkylsilane chains, where the PPy film remains adhered to the underlying coating after a pitting corrosion test.